Contemporary challenges of climate change, sustainable tourism consumption, and destination competitiveness - Ohnmacht, Timo, 1979-; Priskin, Julianna; Stettler, Jürg (Emerald Publishing Limited, 2018)
This volume presents twenty updated and new theories oftravelers decisions and behaviors. It describes the advances in theory construction and practical applications of theory in the disciplines of tourism, hospitality, leisure, and entertainment (THLE) research. The chapters all build on the grand models appearing in these four literature streams during 1965-2015. This approach is comprehensive in both coverage and depth with regard to constructing, testing, and applying theories of travelers decisions and behaviors, which includes original work in updating grand theories and micro (algorithm-conscious and non-conscious based) theories of travelers decisions and behavior. This volume is the first to fully recognize and construct theories across the THLE discipline. This volume describes the synergies, symbioses, and serendipity occurring in THLE behavior. It tears down researchers' parochial fences of what is and is not tourism, hospitality, leisure, and entertainment. The time has arrived to tourism to embrace hospitality, hospitality to embrace tourism, and all to embrace leisure and entertainment, and this volume servesas a catalyst to accomplish this embrace.
Includes index.
Keywords: Tourism -- Environmental aspects.; Climatic changes.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books